Endoscopic endonasal approach to the craniovertebral junction. Issue 1 (14th March 2022) - Halderman, Ashleigh A.; Barnett, Samuel L.
Abstract: The surgical approach to lesions of the ventral craniovertebral junction (CVJ) has evolved significantly in the last several years with the advent of endoscopic skull base surgery. Differing pathologies of the CVJ can result in irreducible compression of the cervicomedullary region. The endoscopic endonasal approach lends itself well to this region due to the ventral location, and while there is a steep learning curve, is a safe and effective way to perform decompression of the cervicomedullary region. Herein, we discuss the anatomy of the CVJ, preoperative evaluation and surgical considerations, our surgical approach, complications, and outcomes.